The Theory of Business Cycles - Fels, Rendigs (Quarterly Journal of Economics, 1952)
Introduction, 25. — I. Criticisms of Schumpeter's theory, 26. — II. Synthesis with Hicks's theory: Juglar cycles, 32. — III. Synthesis with Hicks's theory: Kondratieff and Kitchin cycles, 38. — IV. Summary, 40.